2004
DOI: 10.1523/jneurosci.2513-04.2004
|View full text |Cite
|
Sign up to set email alerts
|

Selection for Cognitive Control: A Functional Magnetic Resonance Imaging Study on the Selection of Task-Relevant Information

Abstract: The complex environment we live in makes it necessary to distinguish relevant from irrelevant information constantly and reliably. The aim of the present study was to investigate the neural substrate underlying the selection of task-relevant information. We devised a new paradigm in which participants had to switch between two different tasks that were instructed by task cues. The task cues had a relevant and an irrelevant cue dimension. In congruent trials, both cue dimensions indicated the same task; in inco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
81
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(96 citation statements)
references
References 41 publications
14
81
1
Order By: Relevance
“…Because focal lesions within this network lead to discrete functional deficits, it will be important to examine the effect that disruption has on perceptual learning. For example, the lateral prefrontal cortex is instrumental in orienting attention, particularly in relation to the selection of task-relevant information (Brass and von Cramon, 2004), as part of an anterior striatum basal ganglia loop involved in visuospatial representation (Hikosaka et al, 2002), whereas neurons within the lateral intraparietal area in nonhuman primates have been shown to integrate probabilistic evidence regarding spatial positions (Yang and Shadlen, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Because focal lesions within this network lead to discrete functional deficits, it will be important to examine the effect that disruption has on perceptual learning. For example, the lateral prefrontal cortex is instrumental in orienting attention, particularly in relation to the selection of task-relevant information (Brass and von Cramon, 2004), as part of an anterior striatum basal ganglia loop involved in visuospatial representation (Hikosaka et al, 2002), whereas neurons within the lateral intraparietal area in nonhuman primates have been shown to integrate probabilistic evidence regarding spatial positions (Yang and Shadlen, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…The role of the IFJ in WM and cognitive control: Uploading relevant rule information As we mentioned before, studies have shown the IFJ to be crucially involved in cognitive control and, more specifically, in task switching (Brass and von Cramon, 2002, 2004a, 2004bBrass et al, 2005;Derrfuss et al, 2005;Dove et al, 2000;Kim et al, 2012;Sylvester et al, 2003). Studies have also observed the IFJ to be involved in interference control and updating (e.g., Braver et al, 1997;de Fockert et al, 2004;Derrfuss et al, 2004Derrfuss et al, , 2005Mead et al, 2002;Roth et al, 2009;Sylvester et al, 2003).…”
Section: The Nature Of Wm Resources: Domain-general Time-based Resourmentioning
confidence: 91%
“…Task switching has been related to a fronto-parietal network (see Kim et al, 2012, for a meta-analysis). In the frontal cortex, one of the regions that have been most consistently observed in neuroimaging studies of task switching is the Inferior Frontal Junction (IFJ; Brass et al, 2005;Brass and von Cramon, 2002, 2004a, 2004bDerrfuss et al, 2005;Dove et al, 2000;Sylvester et al, 2003). The IFJ is situated at the junction of the precentral sulcus and the inferior frontal sulcus and, as such, anatomically perfectly suited for task switching and task management because it is located at the border of the premotor and prefrontal cortices (Brass and von Cramon, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, recent-no trials from the adapted item recognition task have generated specific neural activity in LIFG compared with other frontal regions (Jonides et al, 1998;Nelson et al, 2003). Recently, several researchers have developed other tasks specifically designed to study the neural basis of selecting a task-relevant internal representation among competing alternatives (Brass & von Cramon, 2004;Zhang, Feng, Fox, Gao, & Tan, 2004) and found activation localized to LIFG only under conditions of conflict.…”
Section: Role Of Lifg In Conflict Resolutionmentioning
confidence: 99%